An Analytical Study of Theatre and censorship in Howard Barker’s No End of Blame: Scenes of Overcoming (1981) and Scenes from an Execution (1984) - Midhin, Majeed Mohammed; Obeid, Ahmed Hameed (Dirasat: Human and Social Sciences, 2023)
Objectives: This paper explores the use of history in contemporary British theatre to address issues like marginalization and censorship, focusing on Barker's theatre theory, which diverges from early works by Churchill and Hare. Emphasizing the artist's role and responsibilities, it delves into potential dilemmas faced in the realm of contemporary British theatre. Methods: This study critically analyzes Barker's plays, "No End of Blame: Scenes of Overcoming" (1981) and "Scenes from an Execution" (1984), through the lens of his influential book, "Arguments for a Theatre." Additionally, insights from interviews with the playwright are incorporated to better understand Barker's views on theatre and censorship. Results: Government interference adversely impacts an artist's freedom, creating a dialectical relationship between the artist and the state. In the 1980s, the theme of censorship and restricted expression is portrayed through artist figures in conflict with external forces. Depicting artists as characters not only illustrates the dilemmas, they faced but also serves as a critique of political efforts to suppress voices during that decade. Conclusions: The paper concludes that artists may intentionally conceal opinions to evade censorship, emphasizing the need for artists to balance political demands with personal expression. Unlike peers like Stoppard and Wertenbaker, Barker doesn't advocate a specific ideology in his plays. He views theatre as a space for unleashing individual imagination rather than conveying a message or utilitarian value. The exploration of artists' roles and responsibilities in Barker's plays remains a fertile area for ongoing research and discovery.